Engagement of mental health service users and carers in care planning – Is it meaningful and adding value?. (December 2021) - Scott, Russ; Aboud, Andrew
Objective: Consider whether mental health service users and carers meaningfully engage in care planning and whether care planning adds value to patient care. Conclusion: A review of the meta-analyses and systematic reviews of service users and carers identified many barriers to their meaningful engagement in care planning. No research has demonstrated any measurable benefits or positive outcomes linked to mental health care planning.